Seasonal Occurrence of Sympatric Blue Whale Subspecies: the Chilean and Southeast Indian Ocean Pygmy Blue Whales With the Antarctic Blue Whale - Truong, Gary; Rogers, Tracey L. (Frontiers in Marine Science, 2021)
There are multiple blue whale acoustic populations found across the Southern Hemisphere. The different subspecies of blue whales feed in separate areas, but during their migration to lower-latitude breeding areas each year, Antarctic blue whales become sympatric with pygmy and Chilean blue whales. Few studies have compared the degree of this overlap of the Southern Hemisphere blue whale subspecies across ocean basins during their migration. Using up to 16 years of acoustic data, this study compares the broad seasonal presence of Antarctic blue whales, Chilean blue whales, and Southeast Indian Ocean (SEIO) pygmy blue whales across the Pacific and Indian Oceans. Antarctic blue whales were sympatric with the other two blue whale subspecies during the migrating season of every year. Despite this overlap, Chilean and pygmy blue whale detections peaked earlier during the austral autumn (April–May) while Antarctic blue whale detections peaked later during the austral winter (June). Chilean (Pacific Ocean) and SEIO (Indian Ocean) pygmy blue whales showed similar seasonal patterns in detections despite occurring in different ocean basins. Though we have shown that Antarctic blue whales have the potential to encounter other blue whale subspecies during the breeding season, these distinct groups have remained acoustically stable through time. Further understanding of where these whales migrate will enable a better insight as to how these subspecies continue to remain separate.